2011
DOI: 10.1007/s00464-010-1550-8
|View full text |Cite
|
Sign up to set email alerts
|

Does speed matter? The impact of operative time on outcome in laparoscopic surgery

Abstract: Introduction Controversy exists concerning the importance of operative time on patient outcomes. It is unclear whether faster is better or haste makes waste or similarly whether slower procedures represent a safe, meticulous approach or inexperienced dawdling. The objective of the present study was to determine the effect of operative time on 30-day outcomes in laparoscopic surgery. Methods Patients who underwent laparoscopic general surgery procedures (colectomy, cholecystectomy, Nissen fundoplication, ingu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
87
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(89 citation statements)
references
References 7 publications
2
87
0
Order By: Relevance
“…[9][10][11][12][13][14][15][16][17][18][19][20] This association likely reflects multiple confounding factors, including the observation that complex and challenging cases take longer and are associated with higher complication rates. Disentangling the impact of teaching time from other factors that increase surgical duration will be a considerable challenge for future research to address.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13][14][15][16][17][18][19][20] This association likely reflects multiple confounding factors, including the observation that complex and challenging cases take longer and are associated with higher complication rates. Disentangling the impact of teaching time from other factors that increase surgical duration will be a considerable challenge for future research to address.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has also demonstrated a consistent association between prolonged surgery duration and adverse patient outcomes across a wide range of procedures. [9][10][11][12][13][14][15][16][17][18][19][20] Although previous research has shown that trainee involvement is associated with prolonged surgical duration, [1][2][3][4][5][6][7][8] the magnitude of this increase has not been estimated at a population level, nor has previous research adjusted for patient-and surgeon-related factors, such as experience of the attending surgeon. Administrative data from the province of Ontario are ideal to address this research question because surgical training in Ontario is concentrated within a limited number of teaching hospitals, such that the impact of training on surgery duration can be estimated by comparing teaching and nonteaching hospitals.…”
mentioning
confidence: 99%
“…19,20 Intuitively, longer operative times are associated with increased odds of complications. 21 Operative times for both approaches in our analysis had significant differences in operative times between cases with and without trainees. Moreover, increased complications are associated with increased LOS and overall cost of hospitalization.…”
Section: Discussionmentioning
confidence: 96%
“…"It is unclear whether faster is better or haste makes waste or similarly whether slower procedures represent a safe, meticulous approach or inexperienced dawdling." 1 …”
Section: Introductionmentioning
confidence: 97%